Immunohistochemical Analysis of Histone H3 Modification in Newt Tail Tissue Cells following Amputation - Ji-Wen Wu; Xu Zhang; Reiko Sekiya; Kiyoshi Aoyagi; Tao-Sheng Li (Stem Cells International)
Background. Newts have impressive regenerative capabilities, but it remains unclear about the role of epigenetic regulation in regeneration process. We herein investigated histone modifications in newt tail tissue cells following amputation. Methods and Results. Iberian ribbed male newts (6-8 months old) were suffered to about 1.5 cm length of amputation of their tails for initiating regeneration process, and the residual stump of tail tissues was collected for immunohistochemical analysis 3 days later. Compared to the tissue cells of intact tails, c-kit-positive stem cells and PCNA-positive proliferating cells were significantly higher in tails suffered to amputation (P<0.001). Amputation also significantly induced the acetylation of H3K9, H3K14, and H3K27 in cells of the tails with amputation (P<0.001), but did not significantly change the methylation of H3K27 (P=0.063). Conclusion. These results suggest that epigenetic regulation likely involves in newt tail regeneration following amputation.